2015
DOI: 10.1186/s12906-015-0851-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cyperus esculentus tubers (Tiger Nut) on male rat copulatory behavior

Abstract: BackgroundCyperus esculentus tubers (tiger nut) are one of the ancient food sources known to humanity. It is traditionally used in the Middle East to stimulate sexual arousal in men. However, there has been no scientific evidence about its assumed aphrodisiac properties. This study aimed to investigate the influence of tiger nut on the copulatory behavior of sexually active male rats.MethodsTwo sets of sexually active male rats -highly active and moderately active- were identified depending on baseline sexual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 40 publications
4
37
0
2
Order By: Relevance
“…11 In this study, tiger nut stimulated sexual arousal in rats, which is evident by the reduction in mount frequencies and ejaculatory latencies that have been keenly surveyed. Our observation however, supports the report by Allouh 11 and Allouh et al 15 in which factors being investigated have been considered as parameters for determining increased libido in male rats. Improved libido in animals after ingesting tiger nut extract could be due, in part, to increased serum testosterone levels.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…11 In this study, tiger nut stimulated sexual arousal in rats, which is evident by the reduction in mount frequencies and ejaculatory latencies that have been keenly surveyed. Our observation however, supports the report by Allouh 11 and Allouh et al 15 in which factors being investigated have been considered as parameters for determining increased libido in male rats. Improved libido in animals after ingesting tiger nut extract could be due, in part, to increased serum testosterone levels.…”
Section: Resultssupporting
confidence: 92%
“…Improved libido in animals after ingesting tiger nut extract could be due, in part, to increased serum testosterone levels. 15 Mount frequency and Ejaculatory latency are important parameters for enrichment of sexual desire. Though, mount frequency points at sexual motivation, improved ejaculatory latency displays the comfort by which ejaculatory reflexes are maintained.…”
Section: Resultsmentioning
confidence: 99%
“…Cyperus esculentus L. or tiger nutsedge, also known as Bhadra musta in Sanskrit, is an annual or perennial herb that has been reported as aphrodisiac in Ayurveda (Prakash & Ragavan, ). Allouh, Daradka, and Ghaida () investigated the aphrodisiac properties of C. esculentus in sexually active male rats—highly active and moderately active. They administered 1 and 2 g kg −1 day −1 of C. esculentus to highly active rats and 2 g kg −1 day −1 to moderately active rats and assessed copulatory behaviour and serum hormone levels after 30 days.…”
Section: Medicinal Plants Andplant‐derived Products Used As Aphrodisimentioning
confidence: 99%
“…Though, literatures have implicated CE as sex enhancer [20][21][22], evidence of its much touted tendency to facilitate sexual invigoration is just receiving scientific attention. While Allouh et al [23] have just recently reported the potency of its powdered formulation on the copulatory behaviour of male rats, its androgenic potential is still lacking in scientific literatures. Thus, this study aimed to provide detailed and comprehensive biochemical information on the aphrodisiac potentials of oral administration of crude aqueous extract of C. esculentus in paroxetine-sexually dysfunctioned male Wistar rats.…”
Section: Introductionmentioning
confidence: 99%